Reply to Machina and Deutsch on vagueness, ignorance, and margins for error - Williamson, T (Springer, 2002)
In their paper "Vagueness, Ignorance, and Margine for Error" Kenton Machina and Harry Deutsch criticize the epistemic theory of vagueness. This paper answers their objections. The main issues discussed are: the relation between meaning and use; the principle of bivalence; the ontology of vaguely specified classes; the proper form of margin for error principles; iterations of epistemic operators and semantic compositionality; the relation of lack of it between quantum mechanics and theories of vagueness.